Preparation method and application of sulfur-doped metal single atom-loaded porous carbon material

By using sulfur-doped metal single-atom-loaded porous carbon materials in lithium-sulfur batteries, the problems of polysulfide shuttle effect and reaction kinetics in the battery are solved, and efficient battery performance improvement is achieved.

CN119390053BActive Publication Date: 2025-04-18CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411556818.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-04-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

Lithium-sulfur batteries have low discharge specific capacity and low Coulomb efficiency due to polysulfide shuttle effect and slow reaction kinetics, which hinder their commercialization process.

Method used

By forming stable coordination bonds with the sulfonic acid group, the domain is bounded in the porous structure of zeolite imidazole-8 three-dimensional network, and pyrolysis is obtained to obtain a sulfur-doped metal single-atom-loaded porous carbon material, which uses sulfur atoms to break the symmetry of metal-N4 and improve catalytic activity.

Benefits of technology

Effectively inhibit polysulfide shuttle, improve battery reaction kinetics, improve the utilization rate of active substances of lithium-sulfur batteries, and achieve excellent battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390053B_ABST
    Figure CN119390053B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a sulfur-doped metal single atom-loaded porous carbon material. A metal ion is used to form a stable coordination bond with a sulfonic acid group, which is confined in a three-dimensional network porous structure of zeolite imidazole-8, and a sulfur-doped metal single atom-loaded porous carbon material is obtained by pyrolysis. The material is dodecahedral, with a particle size of 100 to 1000 nm and a metal single atom mass percentage of 0.1% to 10%. In addition, the present invention adjusts the electronic structure of the catalyst active site by sulfur doping, improves the single atom adsorption and catalytic ability, alleviates polysulfide shuttling, improves the electrode conversion reaction kinetics, and realizes a high-performance lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy technology, and specifically relates to a preparation method of a heteroatom-doped metal single atom-loaded porous carbon material and its application in a lithium-sulfur battery. Background Art

[0002] Lithium-sulfur batteries have high energy density (2600 Wh kg -1 ) and low cost, environmental friendliness, etc. have attracted widespread attention. However, the polysulfide shuttle effect and slow reaction kinetics lead to low discharge specific capacity and low coulombic efficiency of the battery, which seriously hinders the commercialization of lithium-sulfur batteries. Therefore, inhibiting polysulfide shuttle and improving battery conversion kinetics are key factors in improving the performance of lithium-sulfur batteries.

[0003] Single atom catalysts (SACS) have excellent adsorption and catalytic activity and have become a new frontier in the research of lithium-sulfur battery cathodes. Generally speaking, the central metal atom is concentrated on the d-block metal and exists in the form of non-polar metal-N4 coordination. Its adsorption and catalytic activity have not yet reached the expected value. Recent studies have shown that the introduction of sulfur atoms in the first coordination layer of the metal can break the symmetry of the planar metal-N4, thereby adjusting the electronic structure of the central metal atom, improving the ability to adsorb polysulfides and catalytic activity, and thus affecting battery performance. However, as a non-metallic element with extremely active chemical properties, sulfur easily reacts with metals to form corresponding sulfides during the reaction process, and it is still challenging to achieve the precise preparation of sulfur-doped metal single atoms. Summary of the invention

[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a sulfur-doped metal single atom-loaded porous carbon material and its application in lithium-sulfur batteries, using metal ions to form stable coordination bonds with sulfonic acid groups, confining them in the three-dimensional network porous structure of zeolite imidazole-8, and obtaining a sulfur-doped metal single atom-loaded porous carbon material by pyrolysis. Sulfur atoms are used to break the symmetry of planar metal-N4, causing electron redistribution, improving the ability of metal centers to adsorb polysulfides and catalytic activity, and achieving excellent battery performance.

[0005] The first object of the present invention is to provide a method for preparing a sulfur-doped metal single atom-loaded porous carbon material, comprising the following steps:

[0006] S1 dissolves zinc nitrate in methanol to obtain a zinc nitrate solution;

[0007] S2 dissolving 2-methylimidazole in methanol to obtain a 2-methylimidazole solution;

[0008] S3 dissolving metal nitrate and organic sulfonic acid in methanol in a certain proportion to obtain a metal salt solution;

[0009] S4: Mix the zinc nitrate solution, 2-methylimidazole solution and metal salt solution, stir at room temperature, at a stirring rate of 50-100 r / min, for a stirring time of 12-24 h, and centrifuge to obtain a precursor powder;

[0010] S5: calcining the precursor powder prepared in step 4 at 900-1200° C. for 1-4 h in an argon protected atmosphere to obtain a sulfur-doped metal single atom-loaded porous carbon material.

[0011] Based on the preparation of sulfur-doped metal single atom-loaded porous carbon materials, the present invention provides a method for preparing sulfur-doped metal single atom-loaded porous carbon materials by utilizing metal ions to form stable coordination bonds with sulfonic acid groups, confining them in the three-dimensional network porous structure of zeolite imidazole-8, and obtaining sulfur-doped metal single atom-loaded porous carbon materials after pyrolysis.

[0012] As a preferred embodiment of the method for preparing the sulfur-doped metal single atom-loaded porous carbon material of the present invention: the mass percentage of carbon in the sulfur-doped metal single atom-loaded porous carbon material is 60% to 99%, the metal single atom content is 0.1% to 10%, the mass percentage of nitrogen is 1% to 40%, and the mass percentage of sulfur is 0.1% to 10%;

[0013] The sulfur-doped metal single atom-loaded porous carbon material is dodecahedral, has a particle size of 100 to 1000 nm, and a specific surface area of ​​500 to 1500 m 2 g -1 , pore volume is 0.1~1 cm 3 g -1 .

[0014] As a preferred embodiment of the method for preparing sulfur-doped metal single atom-loaded porous carbon material of the present invention: in the step S4,

[0015] The concentration of the zinc nitrate solution is 25 mg / mL;

[0016] The concentration of the 2-methylimidazole solution is 25 mg / mL to 100 mg / mL;

[0017] The concentration of the metal nitrate solution is 0.5 mg / mL to 2.5 mg / mL;

[0018] As a preferred embodiment of the method for preparing sulfur-doped metal single atom-loaded porous carbon material of the present invention: in step S3

[0019] The mass ratio of the metal nitrate to the organic sulfonic acid is 1:0.3-1;

[0020] The metal nitrate is any one of iron nitrate, cobalt nitrate, nickel nitrate, cerium nitrate, manganese nitrate, etc.;

[0021] The organic sulfonic acid is one of p-toluenesulfonic acid, isethionic acid, dodecylbenzenesulfonic acid and the like.

[0022] The second object of the present invention is to realize the application of sulfur-doped metal single atom-loaded porous carbon materials in lithium-sulfur batteries.

[0023] The application of sulfur-doped metal single atom-loaded porous carbon material in lithium-sulfur batteries is to use the synthesized sulfur-doped metal single atom-loaded porous carbon material for the sulfur positive electrode to explore its role in the battery. The specific operation steps are:

[0024] 1) Weigh the sublimated sulfur and the sulfur-doped metal single atom-loaded porous carbon material in a mass ratio of 7:3, ball-mill the mixed powder for 2 h, and then put it into an ampoule and seal it. In an argon atmosphere, heat at 155°C for 12 hours to obtain a sulfur-doped metal single atom-loaded porous carbon / sulfur composite material. Mix the sulfur-doped metal single atom-loaded porous carbon / sulfur composite material, acetylene black and polyvinylidene fluoride (PVDF) material in a mass ratio of 7:2:1, grind thoroughly, add an appropriate amount of nitrogen methyl pyrrolidone (NMP) solution and stir for 6 hours to form a uniform slurry. Coat the above slurry on the surface of aluminum foil, dry it in a vacuum oven at 50°C for 24 hours, and then cut it into a circular positive electrode sheet with a diameter of 12 mm for use;

[0025] 2) The prepared sulfur-doped metal single atom-loaded porous carbon / sulfur composite material, polypropylene separator and metal lithium sheet negative electrode were assembled into a lithium-sulfur battery. The electrolyte (containing 1.0 mol / L lithium bistrifluoromethylsulfonyl imide (LiTFSI) and 1 wt% LiNO3 in a volume ratio of 1:1 mixed 1,3-dioxolane and ethylene glycol dimethyl ether solution) was added in an amount of 20 μL on the positive electrode side and 20 μL on the negative electrode side, respectively. The assembled battery was left to stand for 6 hours before electrochemical testing.

[0026] Beneficial effects of the present invention:

[0027] 1) The present invention utilizes metal ions to form stable coordination bonds with sulfonic acid groups, confines them in the three-dimensional network porous structure of zeolite imidazole-8, and obtains sulfur-doped metal single atom-loaded porous carbon materials through pyrolysis. The preparation method is scientific, reasonable, easy to implement, low-cost, and can achieve large-scale production.

[0028] 2) The present invention utilizes sulfur atoms to break the symmetry of planar metal-N4, causing redistribution of electrons in the central atom, thereby improving the ability of single-atom catalysts to adsorb polysulfides and catalytic activity, effectively inhibiting the polysulfide shuttle effect, improving battery reaction kinetics, and thereby improving the utilization rate of active materials in lithium-sulfur batteries, achieving excellent battery performance, and having potential application prospects.

[0029] 3) The sulfur-doped metal single atom-loaded porous carbon / sulfur electrode prepared by the present invention has an initial discharge specific capacity of 1017 mAh / g at a discharge rate of 0.2C. After 100 cycles, it still has a discharge specific capacity of 945 mAh / g, and the capacity retention rate is as high as 92.9%. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a transmission electron microscope (TEM) image of the sulfur-doped metal cobalt-loaded porous carbon material prepared in Example 1;

[0031] Figure 2 This is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of the sulfur-doped metal cobalt-loaded porous carbon material prepared in Example 1;

[0032] Figure 3 X-ray crystal diffraction (XRD) patterns of sulfur-doped metal single atom-loaded porous carbon materials prepared in Examples 1 and 2;

[0033] Figure 4 This is an X-ray crystal diffraction (XRD) image of the Co9S8-loaded porous carbon material prepared in Comparative Example 1;

[0034] Figure 5 This is an X-ray crystal diffraction (XRD) image of the FeS / Fe-loaded porous carbon material prepared in Comparative Example 2;

[0035] Figure 6 is a cycle performance diagram of the battery prepared in Example 1 under a discharge rate of 0.2C;

[0036] Figure 7 This is a cycle performance diagram of the battery prepared in Comparative Example 1 under a 0.2C discharge rate condition;

[0037] Figure 8 This is a cycle performance diagram of the battery prepared in Comparative Example 2 under a 0.2C discharge rate condition. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0041] A method for preparing a sulfur-doped metal single atom-loaded porous carbon material comprises the following steps:

[0042] S1 dissolves zinc nitrate in methanol to obtain a zinc nitrate solution;

[0043] S2 dissolving 2-methylimidazole in methanol to obtain a 2-methylimidazole solution;

[0044] S3 dissolving metal nitrate and organic sulfonic acid in methanol in a certain proportion to obtain a metal salt solution;

[0045] S4: Mix the zinc nitrate solution, 2-methylimidazole solution and metal salt solution, stir at room temperature, at a stirring rate of 50-100 r / min, for a stirring time of 12-24 h, and centrifuge to obtain a precursor powder;

[0046] S5: calcining the precursor powder prepared in step 4 at 900-1200° C. for 1-4 h in an argon protected atmosphere to obtain a sulfur-doped metal single atom-loaded porous carbon material.

[0047] Example 1

[0048] (1) The preparation method of sulfur-doped single-atom cobalt-loaded porous carbon material is specifically carried out in the following steps:

[0049] S1: Add 3.6 g zinc nitrate and 24 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0050] S2: Add 3.6 g 2-methylimidazole and 96 mL methanol into a 150 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0051] S3: 0.087 g of cobalt nitrate and 0.06 g of p-toluenesulfonic acid were added to a 100 mL beaker, 24 mL of methanol was added to the beaker, and the mixture was placed on a stirrer and stirred at 50-100 r / min for 0.5 h to obtain a cobalt nitrate solution;

[0052] S4: Pour the solution prepared in steps 1, 2, and 3 into a 250 mL beaker quickly, stir at room temperature, at a stirring rate of 50-100 r / min, for 24 h, centrifuge, and dry in a vacuum oven at 60 °C for 12 h to obtain a precursor powder;

[0053] S5: The precursor powder prepared in step 4 is calcined at 1000°C for 2 h under an argon atmosphere, and then the obtained powder is ground to obtain a sulfur-doped single-atom cobalt-loaded porous carbon material. The morphology and structure of the material are characterized as follows: Figure 1 , as shown in 2 and 3.

[0054] Figure 1 This is a TEM image of the sulfur-doped single-atom cobalt-loaded porous carbon material. From the image, we can see that the sulfur-doped single-atom cobalt-loaded porous carbon material is dodecahedral in shape, with a particle size of about 500 nm.

[0055] Figure 2 This is the AC-STEM image of the sulfur-doped single-atom cobalt-loaded porous carbon material. From the image, we can see that many bright spots with a diameter of about 0.15 nm are distributed on the carbon substrate, indicating that the cobalt element is loaded on the porous carbon substrate in the form of a single atom.

[0056] Figure 3 The X-ray crystal diffraction (XRD) images of the sulfur-doped metal single atom-loaded porous carbon material prepared in Examples 1 and 2 show two obvious diffraction peaks at about 24° and 44°, respectively. These two peaks correspond to the (002) and (100) crystal planes of graphite. The diffraction peaks are broad, indicating a high degree of disorder. No diffraction peaks of cobalt and its compounds were observed in the image, further demonstrating the successful preparation of sulfur-doped single atom cobalt-loaded porous carbon material.

[0057] (2) Application of sulfur-doped single-atom cobalt-loaded porous carbon materials in lithium-sulfur batteries is carried out in the following steps:

[0058] 1) Weigh 3 g of sublimated sulfur and 1 g of the sulfur-doped single-atom cobalt-loaded porous carbon material, ball-mill for 2 h, put them into an ampoule and seal them, and heat them at 155°C for 12 h in an argon atmosphere to obtain a sulfur-doped single-atom cobalt-loaded porous carbon / sulfur composite material. Put 0.07 g of sulfur-doped single-atom cobalt-loaded porous carbon material / sulfur composite material, 0.02 g of acetylene black and 0.01 g of PVDF into a mortar, grind them thoroughly and pour them into a 2 mL volumetric flask, add about 1 mL of NMP and stir for 6 h to form a uniform slurry. Coat the above slurry on the surface of aluminum foil, dry it in a vacuum oven at 50°C for 24 h, and cut it into a circular positive electrode sheet with a diameter of 12 mm for use;

[0059] 2) In the anhydrous and oxygen-free atmosphere of the glove box, the prepared sulfur-doped single-atom cobalt-loaded porous carbon material / sulfur electrode was placed in the center of the positive electrode shell, and 20 μL of electrolyte ((containing 1.0 mol / L lithium bistrifluoromethylsulfonyl imide (LiTFSI) and 1 wt% LiNO3 in a volume ratio of 1:1 mixed 1,3-dioxolane and ethylene glycol dimethyl ether solution) was added dropwise, and a polypropylene diaphragm with a diameter of 19 mm was placed. 20 μL of the above electrolyte was added, and then a metal lithium sheet with a diameter of 15 mm was placed. After adding a gasket and a shrapnel, the negative electrode shell was covered and assembled into a lithium-sulfur battery after hydraulic pressure. The assembled battery was left to stand for 6 h and then electrochemically tested. The test results are shown in Figure 6 shown.

[0060] Figure 6 This is a cycle performance diagram of the battery prepared in Example 1 under a discharge rate of 0.2C. It can be seen from the figure that the battery has an initial discharge capacity of 1017 mAh / g under a discharge rate of 0.2C, and still has a discharge capacity of 945 mAh / g after 100 cycles, with a capacity retention rate of 92.9%. The excellent capacity retention rate is closely related to the fact that sulfur doping changes the electronic structure of single-atom cobalt, improves its ability to adsorb polysulfides and catalytic activity, thereby effectively inhibiting polysulfide shuttle and improving battery reaction kinetics.

[0061] Example 2

[0062] (1) The preparation method of sulfur-doped single-atom iron-supported porous carbon composite material is specifically carried out in the following steps:

[0063] S1: Add 3.6 g zinc nitrate and 24 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0064] S2: Add 3.6 g 2-methylimidazole and 96 mL methanol into a 150 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0065] S3: Add 0.12 g of ferric nitrate and 0.06 g of p-toluenesulfonic acid into a 100 mL beaker, add 24 mL of methanol into the beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a ferric nitrate solution;

[0066] S4: Pour the solution prepared in steps 1, 2, and 3 into a 200 mL beaker quickly, stir at room temperature at a stirring rate of 50-100 r / min for 24 h, centrifuge, and dry in a vacuum oven at 60°C for 12 h to obtain a precursor powder;

[0067] S5: calcining the precursor powder prepared in step 4 at 1100° C. for 2 h under an argon protected atmosphere, and then grinding the obtained powder to obtain a sulfur-doped single-atom iron-loaded porous carbon material.

[0068] Figure 3 The X-ray crystal diffraction (XRD) diagram of the sulfur-doped metal single atom-loaded porous carbon material prepared in Examples 1 and 2 shows that the sulfur-doped single atom iron-loaded porous carbon composite material has two obvious diffraction peaks, located at about 24° and 44°, respectively. These two peaks correspond to the (002) and (100) crystal planes of graphite. The diffraction peaks are relatively broad, indicating a high degree of disorder. No diffraction peaks of cobalt and its compounds were observed in the figure, further illustrating the successful preparation of the sulfur-doped single atom iron-loaded porous carbon material.

[0069] (2) The steps for realizing the application of sulfur-doped single-atom iron-loaded porous carbon material in lithium-sulfur batteries are the same as those in Example 1.

[0070] Example 3

[0071] (1) The preparation method of sulfur-doped single-atom nickel-loaded porous carbon material is specifically carried out in the following steps:

[0072] S1: Add 3.6 g zinc nitrate and 24 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0073] S2: Add 9 g of 2-methylimidazole and 96 mL of methanol into a 100 mL beaker, place it on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0074] S3: 0.12 g nickel nitrate and 0.12 g hydroxyethyl sulfonic acid were added to a 100 mL beaker, 24 mL methanol was added to the beaker, and the mixture was placed on a stirrer and stirred at 50-100 r / min for 0.5 h to obtain a nickel nitrate solution.

[0075] S4: Pour the solution prepared in steps 1, 2, and 3 into a 200 mL beaker quickly, stir at room temperature at a stirring rate of 50-100 r / min for 24 h, centrifuge, and dry in a vacuum oven at 60°C for 12 h to obtain a precursor powder;

[0076] S5: calcining the precursor powder prepared in step 4 at 1100° C. for 3 h in an argon protected atmosphere, and then grinding the obtained powder to obtain a sulfur-doped single-atom nickel-loaded porous carbon composite material.

[0077] (2) The steps for realizing the application of sulfur-doped single-atom nickel-loaded porous carbon composite material in lithium-sulfur batteries are the same as those in Example 1.

[0078] Example 4

[0079] (1) The preparation method of sulfur-doped single-atom cobalt-loaded porous carbon composite material is specifically carried out in the following steps:

[0080] S1: Add 3.6 g zinc nitrate and 24 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0081] S2: Add 3.6 g 2-methylimidazole and 96 mL methanol into a 150 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0082] S3: Add 0.3 g of cobalt nitrate and 0.2 g of p-toluenesulfonic acid into a 100 mL beaker, add 24 mL of methanol into the beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a cobalt nitrate solution;

[0083] S4: Pour the solution prepared in steps 1, 2, and 3 into a 250 mL beaker quickly, stir at room temperature, at a stirring rate of 50-100 r / min, for 24 h, centrifuge, and dry in a vacuum oven at 60 °C for 12 h to obtain a precursor powder;

[0084] S5: calcining the precursor powder prepared in step 4 at 1000° C. for 2 h in an argon protected atmosphere, and then grinding the obtained powder to obtain a sulfur-doped single-atom cobalt-loaded porous carbon material.

[0085] (2) The steps for realizing the application of sulfur-doped single-atom cobalt-loaded porous carbon composite materials in lithium-sulfur batteries are the same as those in Example 1.

[0086] Comparative Example 1

[0087] The other conditions are the same as those in Example 1, except that the organic sulfonic acid is replaced by 3-mercaptopropionic acid:

[0088] (1) The preparation method of Co9S8 loaded porous carbon composite material is specifically carried out according to the following steps:

[0089] S1: Add 3.6 g zinc nitrate and 24 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0090] S2: Add 3.6 g 2-methylimidazole and 96 mL methanol into a 150 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0091] S3: Add 0.087 g of cobalt nitrate and 0.06 g of 3-mercaptopropionic acid into a 100 mL beaker, add 24 mL of methanol into the beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a cobalt nitrate solution;

[0092] S4: Pour the solution prepared in steps 1, 2, and 3 into a 250 mL beaker quickly, stir at room temperature, at a stirring rate of 50-100 r / min, for 24 h, centrifuge, and dry in a vacuum oven at 60 °C for 12 h to obtain a precursor powder;

[0093] S5: The precursor powder prepared in step 4 is calcined at 1000°C for 2 h under an argon atmosphere, and then the obtained powder is ground to obtain a Co9S8-loaded porous carbon composite material. The structure of the material is analyzed, as shown in FIG. Figure 4 shown.

[0094] Figure 4 The X-ray crystal diffraction (XRD) pattern of the Co9S8-loaded porous carbon material prepared in Comparative Example 1 shows that the diffraction peaks of the sample at 15.4°, 29.8°, 32.0°, 39.2°, 47.5°, and 51.9° completely correspond to the Co9S8 standard X-ray diffraction card JCPDSNO.86-2273. Compared with Example 1, Comparative Example 1 forms obvious metal sulfides, indicating that the type of sulfur source plays an important role in the synthesis of sulfur-doped metal single atoms.

[0095] (2) The steps for realizing the application of Co9S8 loaded porous carbon composite materials in lithium-sulfur batteries are the same as those in Example 1. The performance of the battery at a discharge rate of 0.2C is as follows: Figure 7 shown.

[0096] Figure 7 This is a cycle performance diagram of the battery prepared in Comparative Example 1 under a discharge rate of 0.2C. It can be seen from the figure that the initial discharge specific capacity of the battery under a discharge rate of 0.2C is 794 mAh / g, which is much lower than that of Example 1, further illustrating the important role of sulfur-doped metal single-atom catalysts in lithium-sulfur batteries.

[0097] Comparative Example 2

[0098] The other conditions are the same as those in Example 2, except that the organic sulfonic acid is replaced by 3-mercaptopropionic acid:

[0099] (1) The preparation method of FeS / Fe loaded porous carbon composite material is specifically carried out according to the following steps:

[0100] S1: Add 3.6 g zinc nitrate and 24 mL methanol into a 100 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a zinc nitrate solution.

[0101] S2: Add 3.6 g 2-methylimidazole and 96 mL methanol into a 150 mL beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a 2-methylimidazole solution.

[0102] S3: Add 0.12 g of ferric nitrate and 0.06 g of 3-mercaptopropionic acid into a 100 mL beaker, add 24 mL of methanol into the beaker, place on a stirrer, and stir at 50-100 r / min for 0.5 h to obtain a ferric nitrate solution;

[0103] S4: Pour the solution prepared in steps 1, 2, and 3 into a 200 mL beaker quickly, stir at room temperature at a stirring rate of 50-100 r / min for 24 h, centrifuge, and dry in a vacuum oven at 60°C for 12 h to obtain a precursor powder;

[0104] S5: The precursor powder prepared in step 4 is calcined at 1100°C for 2 h under an argon atmosphere, and then the obtained powder is ground to obtain a FeS-supported porous carbon composite material. The structure of the material is analyzed, such as Figure 5 shown.

[0105] Figure 5 This is the X-ray crystal diffraction (XRD) pattern of the FeS / Fe-loaded porous carbon material prepared in Comparative Example 2. The diffraction peaks of the sample at 29.9°, 33.6°, 43.1°, and 53.2° correspond to the standard X-ray diffraction of FeS. The diffraction peak at 44.8° corresponds well to the standard X-ray diffraction spectrum of Fe element.

[0106] (2) The steps for realizing the application of FeS / Fe loaded porous carbon composite materials in lithium-sulfur batteries are the same as those in Example 1. The performance of the battery at a discharge rate of 0.2C is as follows: Figure 8 shown.

[0107] Figure 8 This is a cycle performance diagram of the battery prepared in Comparative Example 2 under a discharge rate of 0.2C. It can be seen from the figure that the initial discharge specific capacity of the battery under a discharge rate of 0.2C is 720 mAh / g. After 100 cycles, the discharge specific capacity is 450 mAh / g, and the capacity retention rate is 62.5%.

Claims

1. A method for preparing sulfur-doped metal single atom-loaded porous carbon material, characterized in that: The following steps are involved: S1 dissolves zinc nitrate in methanol to obtain a zinc nitrate solution; S2 dissolving 2-methylimidazole in methanol to obtain a 2-methylimidazole solution; S3 dissolving metal nitrate and organic sulfonic acid in methanol in a certain proportion to obtain a metal salt solution; The mass ratio of the metal nitrate to the organic sulfonic acid is 1:0.3-1; The metal nitrate is any one of iron nitrate, cobalt nitrate, nickel nitrate, cerium nitrate, and manganese nitrate; The organic sulfonic acid is one of p-toluenesulfonic acid, isethionic acid, and dodecylbenzenesulfonic acid; S4: Mix the zinc nitrate solution, 2-methylimidazole solution and metal salt solution, stir at room temperature, at a stirring rate of 50-100 r / min, for a stirring time of 12-24 h, and centrifuge to obtain a precursor powder; The concentration of the zinc nitrate solution is 25 mg / mL; The concentration of the 2-methylimidazole solution is 25 mg / mL to 100 mg / mL; The concentration of the metal nitrate solution is 0.5 mg / mL to 2.5 mg / mL; S5: calcining the precursor powder prepared in step 4 at 900-1200° C. for 1-4 h in an argon atmosphere to obtain a sulfur-doped metal single atom-loaded porous carbon material; The sulfur-doped metal single atom-loaded porous carbon material has a carbon mass percentage of 60% to 99%, a metal single atom content of 0.1% to 10%, a nitrogen mass percentage of 1% to 40%, and a sulfur mass percentage of 0.1% to 10%.

2. The method for preparing a sulfur-doped metal single atom-loaded porous carbon material according to claim 1, characterized in that: The sulfur-doped metal single atom-loaded porous carbon material is dodecahedral, has a particle size of 100 to 1000 nm, and a specific surface area of ​​500 to 1500 m 2 g -1 , pore volume is 0.1~1 cm 3 g -1 .

3. The method for preparing a sulfur-doped metal single atom-loaded porous carbon material according to claim 1 or 2, characterized in that: The sulfur-doped metal single atom-loaded porous carbon material is used as a sulfur positive electrode carrier and is applied in lithium-sulfur batteries.

Citation Information

Patent Citations

  • Surface treatment method for carbon material and carbon material

    JP2011001230A

  • Metallic sulphide catalysts, processes for synthesising said catalysts and use thereof

    US20020045539A1